PPP6R3-mediated dephosphorylation regulates mRNA translation during spermatogonial differentiation - Qian Fang; Biyun Liu; Jie Cen; Tongtong Li; Shuhui Ji; Wenqing Li; Gang Lu; Zi-Jiang Chen; Xin Wang; Jianqiang Bao; Hongbin Liu (Communications Biology)
Abstract Protein dephosphorylation mediated by phosphatases regulates spermatogenesis. However, which proteins are dephosphorylated and how they regulate spermatogenesis are largely unknown. Here, we show that germline-specific deletion of protein phosphatase 6 regulatory subunit 3 (PPP6R3), which determines substrate specificity of protein phosphatase 6 (PP6), causes abnormal spermatogonial differentiation and male infertility, accompanied by translation inhibition. PPP6R3 directly interacts with EIF3C and EIF4G1 in KIT+ spermatogonia. Decreased levels of non-phosphorylated EIF3C and EIF4G1 after PPP6R3 deletion attenuate their enrichment for mRNAs associated with spermatogonial differentiation, and increased phosphorylation levels promote their degradation. Specifically, the phosphorylation status both of EIF3CS39 and EIF4G1S1217 are significantly up-regulated in mutant mice. Overexpression of EIF3CS39A and EIF4G1S1217A mutants in Ppp6r3-cKO spermatogonial progenitor cells compensates for the deficiency of differentiation potential by upregulating translation rates of differentiation-associated mRNAs. Our findings demonstrate EIF3C and EIF4G1, as specific substrates of PPP6R3/PP6 holoenzyme, are required for translation activation during spermatogonial differentiation.